Efficacy of online mindfulness for the treatment of insomnia in pregnancy: A randomized clinical trial - Dahee Wi; Rachel Y. Lee; Ira Kantrowitz-Gordon (PLoS ONE, 2025)
Sleep deficiency is common during pregnancy, with consequences for maternal and fetal health. This pilot study assessed the efficacy, feasibility, and acceptability of a six-week, online, mindfulness-based intervention (OPTIMISM) in pregnant women with sleep deficiency. Participants were randomized to either mindfulness (self-directed learning modules about mindfulness meditation, sleep challenges in pregnancy, and behavioral strategies) or education-only control conditions. Participants completed surveys and wore an actigraph with daily sleep diaries for 8 days at baseline and post-intervention. The primary outcome was sleep quality. Secondary outcomes included actigraphy, sleep-related impairment, sleep disturbance, fatigue, depression, anxiety, postnatal depressive symptoms, well-being, and quality of life. Exploratory outcomes included feasibility, acceptability, self-management, and behavior change. Efficacy was estimated with analysis of covariance, comparing mean post-test scores corrected for baseline. Of the 351 women screened, 163 were eligible, 64 enrolled, and 59 were randomized. 45 participants (OPTIMISM, 23; control, 22) completed post-intervention assessments and were included in the analysis. The mean satisfaction with the OPTIMISM was higher than the control group (OPTIMISM, 4.1; control, 3.8). The mean sleep quality score was significantly improved in the OPTIMISM group compared to that in the control group after adjusting for baseline score (OPTIMISM, 5.4; control, 7.6; p =.008; partial h2 =.157). There were similar improvements in sleep-related impairment, sleep disturbance, fatigue, and depressive symptoms, but no differences in other outcomes. Findings suggest that OPTIMISM improves subjective sleep quality and psychological distress, including fatigue, depression, and anxiety during pregnancy and should be tested in larger trials with longitudinal follow-up. Trial registration: ClinicalTrials.gov, NCT04016428. Registered on 11 July 2019.